Alternative RNA splicing of the GIT1 gene is associated with neuroendocrine prostate cancer. Issue 1 (12th December 2018) - Lee, Ahn R.; Gan, Yu; Xie, Ning; Ramnarine, Varune R.; Lovnicki, Jessica M.; Dong, Xuesen
Abstract : Potent androgen receptor pathway inhibition (ARPI) therapies have given rise to a lethal, aggressive subtype of castration‐resistant prostate cancer (CRPC) called treatment‐induced neuroendocrine prostate cancer (t‐NEPC). Now, t‐NEPC poses a major clinical problem as approximately 20% of CRPC cases bear this subtype—a rate of occurrence that is predicted to rise with the widespread use of ARPI therapies. Unfortunately, there are no targeted therapies currently available to treat t‐NEPC as the origin and molecular underpinnings of t‐NEPC development remain unclear. In the present study, we identify that RNA splicing of the G protein‐coupled receptor kinase‐interacting protein 1 ( GIT1 ) gene is a unique event in t‐NEPC patients. Specifically, upregulation of the GIT1‐A splice variant and downregulation of the GIT1‐C variant expressions are associated with t‐NEPC patient tumors, patient‐derived xenografts, and cell models. RNA‐binding assays show that RNA splicing of GIT1 is directly driven by SRRM4 and is associated with the neuroendocrine phenotype in CRPC cohorts. We show that GIT1‐A and GIT1‐C regulate differential transcriptomes in prostate cancer cells, where GIT1‐A regulates genes associated with morphogenesis, neural function, environmental sensing via cell‐adhesion processes, and epigenetic regulation. Consistent with our transcriptomic analyses, we report opposing functions of GIT1‐A and GIT1‐C in the stability of focal adhesions, whereby GIT1‐A promotes focal adhesion stability. In summary, our study is the first to report that alternative RNA splicing of the GIT1 gene is associated with t‐NEPC and reprograms its function involving FA‐mediated signaling and cell processes, which may contribute to t‐NEPC development. Abstract : We report that the alternative RNA splicing of the GIT1 gene is associated with t‐NEPC progression using patient tumor samples, PDX models, and cell models. We demonstrate that GIT1‐A expression is upregulated in NEPC models, whereas expression of GIT1‐C is downregulated when compared to AdPC models, a mechanism regulated by SRRM4‐mediated RNA alternative splicing. Comprehensive transcriptomic data reveal distinct molecular changes in GIT1‐A and GIT1‐C, whereby bioinformatic analyses predict that the GIT1‐A transcriptome is enriched with gene sets implicated in t‐NEPC progression, such as morphogenesis, neural function, environmental sensing via cell‐adhesion processes, and epigenetic regulation. Consistent with our transcriptomic analyses, we report opposing functions of GIT1‐A and GIT1‐C in the stability of focal adhesions, whereby GIT1‐A promotes focal adhesion stability.